The Effect of Platelet-Rich Fibrin on Post-Operative Inflammatory Sequelae after Mandibular Third Molar Surgery: A Randomized Controlled Trial - Azuka Njokanma; Olawunmi Fatusi; Olufemi Ogundipe; Adewale Adejobi; Olasunkanmi Kuye (Nigerian Dental Association, 2023)
Background: Surgical extraction of impacted mandibular third molars is commonly associated with post-operative inflammatory sequelae, causing distress to patients and affecting their quality of life. This study aimed to investigate the effect of using autologous platelet-rich fibrin (PRF) on post-operative pain, facial swelling, and trismus following mandibular third molar surgery. Methods: In this single-blinded prospective randomized controlled trial, 90 participants aged 18-35 years were enrolled. Eligible patients underwent surgical extraction of impacted mandibular third molars under local anesthesia between October 2017 and June 2018 at the Oral and Maxillofacial Surgery clinic of Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria. Participants were randomly assigned to either the PRF group or the non-PRF group. PRF was placed in the extraction socket of the PRF group, while the non-PRF group received a blood clot. Post-operative pain, facial swelling, and trismus were measured as outcomes. Longitudinal data analysis using generalized estimating equations was employed, adjusting for confounding factors, with statistical significance set at p < 0.05. Results: The PRF group exhibited significantly lower pain scores (3.02 mm; p < 0.001), reduced facial swelling (0.55%; p = 0.01), and decreased trismus (4.52%; p = 0.05) compared to the non-PRF group. Conclusion: Placement of PRF in the extraction socket following mandibular third molar surgery resulted in decreased post-operative pain, facial swelling, and trismus. These findings suggest that PRF may have a beneficial impact on the inflammatory outcomes of third molar surgeries.